2020
DOI: 10.15252/embj.2019102931
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD 1‐mediated dNTP degradation is required for efficient DNA repair during antibody class switch recombination

Abstract: Sterile alpha motif and histidine‐aspartic acid domain‐containing protein 1 (SAMHD1), a dNTP triphosphohydrolase, regulates the levels of cellular dNTPs through their hydrolysis. SAMHD1 protects cells from invading viruses that depend on dNTPs to replicate and is frequently mutated in cancers and Aicardi–Goutières syndrome, a hereditary autoimmune encephalopathy. We discovered that SAMHD1 localizes at the immunoglobulin (Ig) switch region, and serves as a novel DNA repair regulator of Ig class switch recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 76 publications
(98 reference statements)
2
33
0
Order By: Relevance
“…As our study reveals that insertions were increased in absence of catalytically active SAMHD1 or in presence of elevated dNTP pools, we propose that super-physiological dNTP levels may increase DNA polymerase resynthesis rates leading to increased refilling of staggered DNA ends and synthesis over inserted DNA templates prior end ligation. Strikingly, our data are in line with a parallel report, addressing SAMHD1 in class switch recombination of antibody constant regions in B cells, which was published during finalization of our manuscript ( 15 ). In this parallel work, it was concomitantly shown that absence of SAMHD1 and high intracellular dNTP levels lead to aberrant insertions at EJ dependent switch junctions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As our study reveals that insertions were increased in absence of catalytically active SAMHD1 or in presence of elevated dNTP pools, we propose that super-physiological dNTP levels may increase DNA polymerase resynthesis rates leading to increased refilling of staggered DNA ends and synthesis over inserted DNA templates prior end ligation. Strikingly, our data are in line with a parallel report, addressing SAMHD1 in class switch recombination of antibody constant regions in B cells, which was published during finalization of our manuscript ( 15 ). In this parallel work, it was concomitantly shown that absence of SAMHD1 and high intracellular dNTP levels lead to aberrant insertions at EJ dependent switch junctions.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we asked whether aside of involvement in homologous DNA repair, SAMHD1 may have an additional effect on NHEJ. Our own results reveal a novel role of SAMHD1 for DNA DSB repair by NHEJ and give new insights into its implication in genome stability and cancer development, and corroborate a very recent report on a novel role of SAMHD1 in regulating class switch recombination in B lymphocytes ( 15 ).…”
Section: Introductionsupporting
confidence: 89%
“…Furthermore, in agreement with the findings in mouse cells, a similar Cas9-based study highlighted the preferential use of 5′ overhangs over 3′ DSBs as substrates for Cas9-mediated CSR and translocations in human cells [73,74], and suggested a differential mode of overhang processing based on break polarity [74]. It has been shown recently that high cellular levels of purine nucleotides shift repair towards an increased use and length of insertions at junctions without affecting microhomology usage, and concomitantly reduce CSR efficiency and Igh translocation frequency [76]. A similar phenotype has been observed during Cas9-mediated CSR of staggered DSBs with 5′ overhangs, but not blunt ends [76].…”
Section: Open Accessmentioning
confidence: 70%
“…It has been shown recently that high cellular levels of purine nucleotides shift repair towards an increased use and length of insertions at junctions without affecting microhomology usage, and concomitantly reduce CSR efficiency and Igh translocation frequency [76]. A similar phenotype has been observed during Cas9-mediated CSR of staggered DSBs with 5′ overhangs, but not blunt ends [76]. Considering that the conversion of AID-generated U:G mispairs generates a considerable portion of staggered DSBs, these findings suggest that insertional repair negatively impacts processing and joining of AID-induced breaks.…”
Section: Open Accessmentioning
confidence: 99%
“…A locus of interest can be isolated by insertion of recognition sequences of DNA-binding molecules, expression of the DNA-binding molecules in the cells, fragmentation of chromatin by sonication or other methods, followed by affinity purification of the DNA-binding molecules bound to the target locus. [4][5][6][7][8][9][10][11][12][13][14] Cross-linking can be performed, if necessary. The locus tagged with the recognition sequences of the DNA-binding molecules can also be isolated by cross-linking, if necessary, fragmentation, and incubation with recombinant or synthetic DNA-binding molecules before affinity purification of the DNA-binding molecules bound to the target locus.…”
Section: Introductionmentioning
confidence: 99%